Performance Analysis and Simulation of Deformation Wheeled Mobile Robot - Lingya Zhao; Yingjian Wang; Hongwei Liu (Jixie chuandong)
A kind of mobile robot with deformation wheel is designed, the conversion between wheel structure and three spoke arc leg structure is realized by controlling the steering gear. On the basis of the working principle of the deformation wheel, the kinematic modeling and the analysis of the obstacle surmounting ability are carried out. The dynamic simulation of the obstacle surmounting ability of the deformation wheel mobile robot is carried out by using Adams software, the correctness of the kinematic analysis is verified, and the motion law curves of displacement, velocity and acceleration are obtained. The finite element simulation of the deformation wheel is carried out by using Abaqus software, and the stress-strain diagram is obtained and vibration mode diagram. The analysis shows that the strength, stiffness and vibration of the mobile robot meet the design requirements. The theoretical analysis has important reference value for the research of mobile robot with deformed wheels.